THE PROBLEMS OF ORGANIZATION OF PUBLIC FOOD IN THE TOURIST INDUSTRY OF THE CRIMEA PENINSULA - M. A. Boyarkina (Современная наука и инновации)
This article examines the main types of tourist recreation on the Crimean peninsula. The problems in the field of organizing cultural tourism recreation, namely in the organization of catering establishments located near the museum and exhibition complexes, have been identified.